Analisis Kebutuhan Belajar Bahasa Inggris Mahasiswa Jurusan Bimbingan dan Konseling Universitas Ma’soem - Aip Syaepul Uyun; Niara Haura Sinta (Ma'soem University, 2023)
ESP (English for Specific Purposes), is a term that refers to the practice of teaching English at the university level, where English is learned not only for communication needs, but also as part of their needs in the world of work. Therefore, the developed curriculum needs to be adapted to the needs of students. However, in practice, teaching ESP in the Guidance and Counseling department Masoem University has not been fully practiced as it should be. This is based on the initial research that has been done. English even tends to be taught like in public schools. Therefore it is necessary to do a needs analysis to find out what learning needs are needed by students majoring in Counseling Guidance. needs analysis was carried out using questionnaires and interviews as well as document analysis. From the research conducted, it was found that the majority of Guidance and Counseling students needed to learn to speak English and increase listening comprehension.